Regional Disparities in Transplantation With Deceased Donor Kidneys With Kidney Donor Profile Index Less Than 20% Among Candidates With Top 20% Estimated Post Transplant Survival. (December 2019) - Husain, S. Ali; King, Kristen L.; Dube, Geoffrey K.; Tsapepas, Demetra; Cohen, David J.; Ratner, Lloyd E.; Mohan, Sumit
Introduction: The Kidney Allocation System in the United States prioritizes candidates with Estimated Post-Transplant Survival (EPTS) ≤20% to receive deceased donor kidneys with Kidney Donor Profile Index (KDPI) ≤20%. Research Question: We compared access to KDPI ≤ 20% kidneys for EPTS ≤ 20% candidates across the United States to determine whether geographic disparities in access to these low KDPI kidneys exist. Design: We identified all incident adult deceased donor kidney candidates wait-listed January 1, 2015, to March 31, 2018, using United Network for Organ Sharing data. We calculated the proportion of candidates transplanted, final EPTS, and KDPI of transplanted kidneys for candidates listed with EPTS ≤ 20% versus >20%. We compared the odds of receiving a KDPI ≤ 20% deceased donor kidney for EPTS ≤ 20% candidates across regions using logistic regression. Results: Among 121 069 deceased donor kidney candidates, 28.5% had listing EPTS ≤ 20%. Of these, 16.1% received deceased donor kidney transplants (candidates listed EPTS > 20%: 17.1% transplanted) and 12.3% lost EPTS ≤ 20% status. Only 49.4% of transplanted EPTS ≤ 20% candidates received a KDPI ≤ 20% kidney, and 48.3% of KDPI ≤ 20% kidneys went to recipients with EPTS > 20% at the time of transplantation. Odds of receiving a KDPI ≤ 20% kidney were highest in region 6 and lowest in region 9 (odds ratio 0.19 [0.13 to 0.28]). The ratio of KDPI ≤ 20% donors per EPTS ≤ 20% candidate and likelihood of KDPI ≤ 20% transplantation were strongly correlated ( r 2 = 0.84). Discussion: Marked geographic variation in the likelihood of receiving a KDPI ≤ 20% deceased donor kidney among transplanted EPTS ≤ 20% candidates exists and is related to differences in organ availability within allocation borders. Policy changes to improve organ sharing are needed to improve equity in access to low KDPI kidneys.